2018
DOI: 10.4314/ahs.v18i4.37
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sap prevalence and biofilm formation among resistant clinical isolates of Candida albicans

Abstract: BackgroundFungal infections represent a serious health problem especially in immunocompromised individuals. Candida albicans is the most common fungi that cause superficial and systemic infections with high mortality rates. Anti-fungal resistance of C. albicans may be attributed to its virulence. Biofilm formation and proteolytic activity are major virulence determents that may influence both pathogenicity and anti-fungal resistance of Candida albicans.ObjectiveThis work studied the relation between biofilm fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 34 publications
3
26
1
Order By: Relevance
“…In some reports from Iran, the incidence of VVC was 5-10%, 12 33.3% 13 and 47.3%. 5 We found that the frequency of VVC in our study is higher than the rates found in Nigerian [14.0%], Indian [20.47%], and Turkish [16%] studies. 1,23,25 In the present study, the species distribution of C. albicans isolates was similar to the study of Shi et al and Yano et al 11,12 There are limited data regarding the antifungal susceptibility of yeast species causing VVC.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In some reports from Iran, the incidence of VVC was 5-10%, 12 33.3% 13 and 47.3%. 5 We found that the frequency of VVC in our study is higher than the rates found in Nigerian [14.0%], Indian [20.47%], and Turkish [16%] studies. 1,23,25 In the present study, the species distribution of C. albicans isolates was similar to the study of Shi et al and Yano et al 11,12 There are limited data regarding the antifungal susceptibility of yeast species causing VVC.…”
Section: Discussioncontrasting
confidence: 68%
“…Resistance of candida species against antifungal agents can infect approximately 5% of women at least four times a year. [3][4][5] The causes of the increasing incidence of VVC could be lowdosage azole maintenance regimens and the use of antifungal agents such as Fluconazole without a prescription. [6][7][8] Predisposing factors for VVC include reproductive age, use of contraceptive steroid medications and bacterial antibiotics, and being diabetic, pregnant, or immunocompromised.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of certain virulence factors was found to be closely related to Sap, which is related to biofilm production as described by Kadry et al (2018). Isolates that were found to be resistant to three different anti-fungal drugs were reported as strong biofilm producers and shown to possess proteolytic activity as they contained either Sap9 or Sap10, or both (Černáková et al, 2019).…”
Section: Biofilmsmentioning
confidence: 97%
“…Previous studies revealed a correlation between prevalence of SAP9 and SAP10 genes and the strong biofilm producers by C. albicans isolates, as 66.7% of these isolates have both Sap9 and Sap10. Sap 9 and Sap10 enzymes maintain cell surface integrity of the Candida cell wall and promote biofilm formation [113]. Recent studies have found that patients infected with fluconazole-resistant C. albicans can enhance the Sap production when treated with this drug [110].…”
Section: Invasive Enzymesmentioning
confidence: 99%